![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
=> ( 6 - 9 ) x | x - 3 | =-21
=> - 3 x | x - 3 | = -21
=> | x - 3 | = -21 : -3 = 7
=> x - 3 = 7 hoặc x - 3 = -7
với x- 3 = 7 => x = 7+3=10
với x - 3 = -7 => x = -7 + 3 =-4
\(\Rightarrow\left|x-3\right|\times\left(6-9\right)=-21\)
\(\Rightarrow\left|x-3\right|\times\left(-3\right)=-21\)
\(\Rightarrow\left|x-3\right|=-21\div\left(-3\right)\)
\(\Rightarrow\left|x-3\right|=7\)
\(\Rightarrow\orbr{\begin{cases}x-3=7\\x-3=-7\end{cases}\Rightarrow\orbr{\begin{cases}x=10\\x=-4\end{cases}}}\)
KL \(\orbr{\begin{cases}x=10\\x=-4\end{cases}}\)Để 6| x - 3 | - 9| x - 3 |=-21
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3x = 32 . 9
3x = 32 . 32
3x = 34
=> x = 4
b) ( 21 + x ) : 9 = 95 : 94
(21 + x ) : 9 = 9
21 + x = 9 . 9
21 + x = 81
x = 81 - 21
x = 60
c) 5x + 1 - 13 = 613
5x = 613 + 13 - 1
5x = 625
5x = 54
=> x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (9.x-21) : 3 = 2
=>9x-21=6
=>9x=27
=>x=3
b, (x-39)-21=0
=>x-39-21=0
=>x-60=0
=>x=60
c, 231+(312-x)=531
=>231+312-x=531
=>543-x=531
=>x=543-531
=>x=12
d, 53.(9-x)=53
=>9-x=1
=>x=8
a/ \(\frac{\left(9x-21\right)}{3}=2\)
\(\Rightarrow9x-21=2\cdot3=6\)
\(\Rightarrow9x=6+21=27\)
\(\Rightarrow x=\frac{27}{9}=3\)
b/ \(\left(x-39\right)-21=0\)
\(\Rightarrow x-39=0+21=21\)
\(\Rightarrow x=21+39=60\)
c/ \(231+\left(312-x\right)=531\)
\(\Rightarrow312-x=531-231=300\)
\(\Rightarrow x=312-300=12\)
d/ \(53\cdot\left(9-x\right)=53\)
\(\Rightarrow9-x=\frac{53}{53}=1\)
\(\Rightarrow x=9-1=8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
6|x - 3| - 9|x - 3| = 21
(6 - 9)|x - 3| = 21
- 3|x - 3| = 21
=> |x - 3| = - 7
Vì |x - 3| ≥ 0 mà - 7 < 0
=> x = rỗng
6|x-3|- 9|x-3|=21
(6-9).|x-3|=21
(-3).|x-3|=21
|x-3|=21:(-3)
|x-3|=-7
|x-3| >hoặc = 0
=> |x-3|=-7 là điều vô lí
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{3}{5}:\dfrac{7}{5}=\dfrac{3}{5}\cdot\dfrac{5}{7}=\dfrac{3}{7}\)
b: \(=\dfrac{9}{17}\left(\dfrac{8}{5}-\dfrac{3}{5}\right)+\dfrac{8}{17}\)
=9/17+8/17=1
c: =>x-3/10=7/15*1/5=7/75
=>x=7/75+3/10=59/150
21:x+3=x:3+9
<=>\(\frac{21}{x}+3=\frac{x}{3}+9\)
ĐKXĐ:x khác 0
=>63+9x=x2+27x
<=>x2+27x-9x-63=0
<=>x2-18x-63=0
<=>x2-21x+3x-63=0
<=>x(x-21)+3(x-3)=0
<=>(x-21)(x+3)=0
<=>x-21=0 hoặc x+3=0
<=>x=21 hoặc x=-3
Vậy x={-3;21}